Pengaruh Promosi, Kualitas Produk dan Harga terhadap Keputusan Pembelian Produk Make Over di Linda Kosmetik Cabang Letkol Iskandar Kota Palembang - Erin Meilisia; Nyimas Artina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid growth of the cosmetics retail industry in Palembang has intensified competition among brands and retailers, requiring a better understanding of the factors influencing consumer purchasing decisions. This study aims to examine the effect of promotion, product quality, and price on purchasing decisions for Make Over products at Linda Kosmetik, Letkol Iskandar Branch, Palembang. A causal quantitative approach was employed using a survey of 342 consumers selected through the Slovin formula. Data were collected through structured questionnaires measured on a Likert scale and analyzed using multiple linear regression with SPSS. The results indicate that promotion (Sig. 0.049), product quality (Sig. 0.000), and price (Sig. 0.000) each have a significant partial effect on purchasing decisions. Simultaneously, the three variables significantly influence purchasing decisions (F = 124.918; Sig. 0.000). The adjusted R square value of 0.592 shows that 59.2% of the variation in purchasing decisions can be explained by promotion, product quality, and price, while the remaining 40.8% is influenced by other factors beyond this model. These findings highlight the importance of integrating competitive pricing, consistent product quality, and effective promotional strategies in retail cosmetics marketing.